Effects of Heparin Therapy on Fibrinolysis in Patients with Pulmonary Embolism - Minnema, M C; ten Cate, H; Beek, E J R van; Ende, A van den; Hack, C E; Brandjes, D P M (Thrombosis and Haemostasis, 1997)
Previous investigations suggested that heparin administration to humans enhances the tissue type plasminogen activator (tPA) levels in blood, but it remains uncertain whether this effect induces fibrinolysis. We studied the effect of therapeutic levels of heparinization on plasma markers for fibrinolysis in patients suspected of pulmonary embolism (PE). Blood samples were taken from 49 consecutive patients; 28 had confirmed PE, 21 had PE excluded.On admission, the plasma levels of plasmin-α2antiplasmin complexes and D-dimer were significantly higher in the patient group with PE compared to those in whom PE was excluded. After heparinization the tPA levels increased in both groups, showing that this effect was not dependent on the initial level of activity of fibrinolysis. In spite of this increment in tPA levels, the concentrations of plasmin-α2antiplasmin complexes and D-dimer decreased.In conclusion, although heparinization in patients with or without pulmonary embolism does lead to elevated tPA: Ag levels, this is not accompanied by enhanced fibrinolysis.